Post-COVID-19 e-learning acceptance and its impact on community college students in Kelantan, Malaysia: A quantitative analysis - Rahman, Azira Hanani Ab; Yaacob, Md Nazrun; Samad, Nur Syafiqah A; Mohamad, Siti Rohana; Sabri, Nur Ain Ayunni (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of this study is to explore the relationship between student motivation, student mindset, computer competency, and behavioural intention to continue using e-learning in the post-COVID-19 era among students at the community colleges in Kelantan, Malaysia. This quantitative study used a self-administered online survey questionnaire, and a convenience sampling method was employed to reach the respondents. Partial least square structural equation modelling (SmartPLS) 4.0 was then used for data analysis. The results of the current study reveal that community college students have a high behavioural intention to continue using e-learning in the post-COVID-19 era, and that behavioural intention positively correlates with student motivation and computer competency. However, there is limited evidence to support the relationship between student mindset and their behavioural intention to continue using e-learning in the post-COVID-19 era. Practically, the findings from this study can be an essential landmark to the management of Community Colleges in determining the direction of future learning in community colleges.